Grade Inflation Rates among Different Ability Students - Mc Spirit, Stephanie; Jones, Kirk E. (Education Policy Analysis Archives, 1999)
This study compares grade inflation rates among different ability students at a large, open admissions public University. Specifically, this study compares trends in graduating grade point average (GPA) from 1983 to 1996 across low, typical and higher ability students. This study also tests other explanations for increases in graduating GPA. These other explanations are changes in 1) ACT score 2) gender 3) college major and 4) vocational programs. With these other explanations considered, regression results still report an inflationary trend in graduating GPA. Time, as measured by college entry year, is still a significant positive predictor of GPA. More directly, comparisons of regression coefficients reveal lower ability students as experiencing the highest rate of grade increase. Higher grade inflation rates among low aptitude students suggest that faculty might be using grades to encourage learning among marginal students.